STRATEGI PELAYANAN PENANAMAN MODAL - Ma'ruf, Ahmad (Jurnal Ekonomi & Studi Pembangunan, 2010)
In order to increase investment, required strong institution. One of the government's efforts to encourage improvement of an investment climate by creating integrated services in a door for investment. The study is aimed formulate a strategy of the service of capital investment, case studies in the office of the Investment Coordinating Body (BKPM) Yogyakarta Special Region (DIY). The data that were used in the studies are primary and secondary data. The primary data obtained from the survey results, observations, depth interview and focus group discussion (FGD). Engineering analysis using descriptive analysis and qualitative analysis had undertaken to formulate service strategies through the SWOT method. Strategy formulation of the results of this study is a strategy for the creation of institutional and quality management system of the BKPM office of DIY Province; such as building a quality management system by carrying out the concept of Total Quality Service (TQS) with certified quality management of the International Standards Organization (ISO); develop institutional IT-based services; develop strategic partnerships; improving public participation in monitoring and evaluation services. Additionally, strategies are needed to encourage the development of human-resource capacity with competence base through the proactive way to send human resources at a certified training.